Determination of inorganic elements in pine pollen by ICP-MS and safety and health risk assessment - Hao LIU; Haitao GUO; Aixi JI; Shuqi LI; Shaojun YU; Guohua YANG; Zhuoer LIU; Yonggang LIU (Journal of Hebei University of Science and Technology)
In order to determine the content of 18 inorganic elements in pine pollen and evaluate the safety and health risks of heavy metals and harmful elements, the samples were treated by microwave digestion method, and then determined by ICP-MS method. The characteristic spectra and correlation coefficient matrix of inorganic elements in pine pollen were drawn by Origin 2021 and Micro-Signal platform. The safety of pine pollen was evaluated by calculating the single pollution index Pi of heavy metal elements. The daily maximum tolerable dose, target hazard quotient and carcinogenic risk of heavy metal elements were calculated to evaluate the health risk of pine pollen. The results show that pine pollen mainly contains six inorganic elements: Na, Mg, K, Ca, Fe and Zn. The results of Pi show that the pine pollen samples are not contaminated and the level is excellent. The heavy metals and harmful elements in pine pollen samples do not pose health risks to the exposed population. The determination and analysis of 18 inorganic elements in pine pollen by ICP-MS method provides a theoretical basis for the quality and safety evaluation and further application of pine pollen.